Membangun Moderasi Beragama di Desa Air Anyir - Adib, Noblana; Irawan, Dody; Fajrin, Rulli; Sanawiyah, Nelly (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Religious moderation is rejecting extremism and liberalism in religion is the key to balance, for the sake of maintaining civilization and creating peace. Air Anyir Village as the location for this community service is located in Merawang District, Bangka Regency, where there is a suspected terrorist who was arrested by Densus 88. Action research as an alternative method of service in community empowerment studies and actions. This action research is based on the assumption that research should be linked to a change agenda in society. The mentoring approach used in this community service is PAR (Participatory Action Research) to change the people's way of thinking, which at first might think exclusively and then have moderate thoughts in religion and nation or at least strengthen the religious moderates they already have. This community service activity is carried out by making classes in the mosque and the theme of religious moderation in Air Anyir village as the material. The results and changes obtained in the fostered subjects are quite good, namely the awareness of moderation in the nation and state. Religious moderates in society can be well developed, and the moderates they have believed in since the beginning are getting stronger. Keywords: Moderation, Religious, Air Anyir